MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN EKONOMI MELALUI MODEL PEMBELAJARAN TPS DENGAN TALKING STICK - Handayani, Uri; Sulistyarini, Sulistyarini; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis entitled â€œ Improving Studentsâ€™ Activeness in learning Economy Through TPS with Talking Stickâ€.The purpose of this study is to increase student activity during the learning process. This type of research is classroom action research with research subjects class X B totaling 32 students. This research was carried out in two cycles, each cycle consisting of 4 stages: (Planning), (Implementation), (Observation), and (Reflection). Methods Data collection techniques use observation. Data collection tools used in the form of student activity sheets during the learning process. The results of the research that have been carried out show that there is an increase in student activity, between Pre cycle, cycle I to cycle II, the overall average activity of students during the cycle is 29.97% increasing in cycle 1 as much as 20% to 50.37% then experiencing an increase in cycle 2 by 18% to 68 54% of the data obtained can be concluded that by using the Think Pair Share learning model with Talking Stick can increase student activity seen from student learning activitiesÂ Keywords:Â  Think Pair Share Learning Model with Talking Stick, Student Activity